Neural network models for speech inteligibility assessment in university classroom - Paulraj, M. P.; Ahmad Nazri; Sivanandam, S.N.; Thagirarani, M. (Kongu Engineering College, 2009)
Organized by Kongu Engineering College, 3rd - 5th January 2008 at Kongu Engineering College, Tamilnaidu, India.